The Impact of Disruptive Technologies on Higher Education in Indonesia - Ishaq, Usep Mohamad (IJIE (Indonesian Journal of Informatics Education), 2021)
This paper will analyze the extent of predictions to what extent the disruption predicted by Christensen has influenced the dynamics of universities in Indonesia and whether we have readiness in facing the disruption era and what strategies need to be taken so that universities can survive and carry out their role as important educational institutions in National development. The method used in this study is to study literature and collect quantitative data from various official sources including official reports from the Indonesian Ministry of Research and Technology and Higher Education and then process the data. The result of the study shows that disruptive technology has a negative impact only on learning institutions closely related to specific professions. However, the impact not so much shown in general.